Plasmid-mediated high-level resistance to erythromycin in Escherichia coli. - Andremont, A (1986)
Escherichia coli BM2195 was found to be resistant to high levels of erythromycin. This new resistance phenotype was due to the constitutive synthesis of an erythromycin esterase which inactivates the antibiotic. The gene conferring resistance to erythromycin in this strain is carried on a 61-kilobase self-transferable plasmid, pIP1100, belonging to incompatibility group X.